She Helps Me All the Time Underestimating Women's Economic Engagement in Rural Honduras - Muller, Miriam (World Bank E-Library Archive, 2020)
This study aims to understand women's engagement in economic activities in rural Honduras and why these activities may not be accurately reflected in official statistics. The study finds that women underreport their engagement in economic activities, including production for own consumption, production of market goods, and remunerated services and commerce. Simulations suggest that the rural female labor force participation rate in Honduras is likely to be underestimated by 6 to 23 percentage points. Two main explanations are found. First, women identify themselves (and are identified) primarily as housewives, and the concepts of housework and employment are taken as mutually exclusive. Second, given this duality between housework and employment, women define "employment" based on a set of necessary characteristics that exclude many of their own activities. Specifically, work needs to (i) be conducted physically outside the home; (ii) be in exchange for money; and (iii) entail sufficient time commitment. Importantly, these conditions are not binding constraints for men to identify their own activities as economic activity. These results have implications for understanding the low labor force participation of women in rural communities in countries beyond Honduras, suggesting that low rates obscure a significant amount of economic activity in many countries